Pendampingan Aktivitas Guru dalam Melaksanakan Gerakan Literasi Sekolah di SMP Kabupaten Karanganyar - Atikah Anindyarini; Sumarwati Sumarwati; Edy Suryanto; Slamet Slamet; Laila Fitri Nur Hidayah; Alifia Nur Aini; Asri Kamila Ramadhani; Yadia Rahma; Maulana Danar (BADAN PENERBIT STIEPARI PRESS, 2025)
This community service aims to provide training and mentoring to develop scenarios for implementing the literacy movement in schools for Indonesian language teachers at junior high schools in Karanganyar Regency. Partners in this activity are the Karanganyar Regency Education and Culture Office and the Indonesian Language Group (MGMP) in Karanganyar. Participants in this community service activity are limited to 30 Indonesian language junior high school teachers representing the Central Working Group in Karanganyar Regency. This research uses a qualitative descriptive method with a participatory approach. The implementation methods include expository, discussion, question and answer sessions, assignments, and guidance. The results of the program implementation show high teacher enthusiasm in participating in material presentation activities from resource persons and question and answer sessions. This is indicated by teacher attendance reaching 100 percent, teachers who submitted assignments at 90%, and teachers who were able to compile assignments well at 85%. In addition to developing scenarios for implementing the School Literacy Movement, teachers also mentioned obstacles faced in implementing GLS, including students' lack of interest and motivation to read, preferring to read short texts, lack of support from parents, and less attractive book collections in the library.